1997
DOI: 10.1177/036354659702500216
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Alignment in the Immobilized Football Player

Abstract: We investigated the effect of football helmet removal on the sagittal alignment of the cervical spine. A quantitative radiographic assessment of relative cervical spine position in subjects immobilized to a standard backboard wearing shoulder pads either with or without a helmet was performed. Comparison was made to a control situation with subjects on a backboard wearing no equipment. Ten subjects were studied using lateral computed tomographic scout films; each subject served as his own control. Radiographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Question 2b: Are outcomes after CSI likely to be better when the helmet/shoulder pads are removed prior to transport? The systematic review identified studies 22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (N ¼ 18) of both static cervical alignment and dynamic cervical motion during immobilization in American tackle football, ice hockey, and lacrosse players. No studies directly examined patient outcomes.…”
Section: Stage 1: Delphi Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Question 2b: Are outcomes after CSI likely to be better when the helmet/shoulder pads are removed prior to transport? The systematic review identified studies 22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (N ¼ 18) of both static cervical alignment and dynamic cervical motion during immobilization in American tackle football, ice hockey, and lacrosse players. No studies directly examined patient outcomes.…”
Section: Stage 1: Delphi Processmentioning
confidence: 99%
“…Comparisons of alignment and motion were made between participants wearing full equipment (helmet and shoulder pads), wearing shoulder pads but no helmet, and wearing no equipment. Studies 27,28,[31][32][33][34]36,40 involving American tackle football and ice hockey equipment did not indicate statistically significant differences in either static cervical alignment or dynamic cervical motion when comparing participants wearing full equipment with participants wearing no equipment. Removal of the football or ice hockey helmet alone, without removing shoulder pads, resulted in cervical alignment that was statistically significantly different from alignment when not wearing any equipment, with greater cervical lordosis seen when only the helmet is removed.…”
Section: Stage 1: Delphi Processmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Studies in other helmeted sports such as football and hockey have helped create guidelines for the emergency transportation of athletes with suspected head/neck injuries regarding the appropriate timing and location of helmet removal. [15][16][17][18] To date there have been no studies that address this issue for alpine winter sports, and ski patrollers currently must rely solely on clinical judgement to decide when to remove a helmet rather than scientific evidence, leading to potential confusion and variation in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Acceptable alignment of the cervical spine when both the helmet and shoulder pads were present provided further evidence to maintain on-field equipment. 15 , 16 However, the recently updated NATA consensus statement now advocates for the removal of equipment under the appropriate conditions before transfer to an emergency medical facility. 10 The NATA noted the advancement of equipment technology, expertise in removing equipment by athletic trainers, and expedited access to the athlete (specifically the chest) as rationales for early equipment removal.…”
mentioning
confidence: 99%